2019
DOI: 10.1111/wvn.12375
|View full text |Cite
|
Sign up to set email alerts
|

A Multisite Health System Survey to Assess Organizational Context to Support Evidence‐Based Practice

Abstract: Background: Implementation and sustainability of a culture of evidence-based practice (EBP) require a systematic approach. A baseline assessment of the organizational context can inform implementation efforts.Aims: To examine organizational hospital context and provider characteristics associated with EBP readiness and to describe EBP context across hospitals.Methods: A nonexperimental descriptive correlational design was used to conduct a webbased survey of direct-care registered nurses (N = 701) and nurse ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 22 publications
2
27
0
4
Order By: Relevance
“…Finally, urgency, e ciency, and immediacy of delivery of healthcare services can be viewed as a positive effect modi er on nurses' workplace social capital. Research supports the notion of higher workplace social capital among nursing professionals working in critical care hospitals compared with those working in community or academic hospitals [31].…”
Section: Determinants Of Nurses' Workplace Social Capital and Their Rmentioning
confidence: 55%
See 1 more Smart Citation
“…Finally, urgency, e ciency, and immediacy of delivery of healthcare services can be viewed as a positive effect modi er on nurses' workplace social capital. Research supports the notion of higher workplace social capital among nursing professionals working in critical care hospitals compared with those working in community or academic hospitals [31].…”
Section: Determinants Of Nurses' Workplace Social Capital and Their Rmentioning
confidence: 55%
“…Shin and Lee [32] reported that the score of workplace social capital varied among nurses' groups with different levels of education, years of experience and years in the present unit. The scores of workplace social capital perceived by nurses with a graduate degree, providing direct care (work role) and having full-time employment status were lower than those who had bachelor's education, provided non-direct care and had part-time/casual work employment [31]. Moreover, employees with higher emotional intelligence are more dexterous in establishing constructive communication [33], in their interactions with others [34] and in developing interpersonal relational networks [35].…”
Section: Determinants Of Nurses' Workplace Social Capital and Their Rmentioning
confidence: 99%
“…The EBP knowledge/ skill variable is also one of the clinical nurse demographic factors that carried out at different times and places that will determine the various findings. By referring to Hauck, Winsett, and Kuric, 2013;Pittman et al, 2019. The level of education also influences EBP knowledge.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
“…Hence, other factors that influence knowledge related to demographics are also sourced in the length of work (Al-Busaidi et al, 2019) so that in studies that use the following two simultaneously variables use filed multilevel regression submission, changed with more pure variables. In research conducted (Pittman et al, 2019). Suggesting young nurses is more difficult in the application of new tactics, and discussed in other demographic discussions such as age and year-old obtained from the results of Dalheim et al, 2012. Other factors were revealed by (Majid et al, 2011;Dalheim et al, 2012;Weng, Kuo, Yang, Liao, et al, 2013;Khammarnia et al, 2015;Gifford et al, 2018) had difficulty find and interpret scientific journals both because of language differences, lack of understanding of statistics and use of scientific terms in research.…”
Section: Implementation Of Ebp Nurses On An Individual Levelmentioning
confidence: 99%
See 1 more Smart Citation